2021
DOI: 10.1177/1040638720985242
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of single-cell next-generation sequencing for determination of intratumoral heterogeneity of canine osteosarcoma cell lines

Abstract: Osteosarcoma (OSA) is a highly aggressive and metastatic neoplasm of both the canine and human patient and is the leading form of osseous neoplasia in both species worldwide. To gain deeper insight into the heterogeneous and genetically chaotic nature of OSA, we applied single-cell transcriptome (scRNA-seq) analysis to 4 canine OSA cell lines. This novel application of scRNA-seq technology to the canine genome required uploading the CanFam3.1 reference genome into an analysis pipeline (10X Genomics Cell Ranger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Among the gene changes they confirmed using RT-qPCR and IHC analysis, we also saw elevated expression of MMP3, SLC2A1, DKK3, POSTN, and ASPN in OSA tumors compared to normal bone samples. A recent article reported loss of PTEN expression in canine OSA cell lines (POS/HMPOS) but continued expression of RB1 in all four tested cell lines 30 . WES analysis of 8 canine OSA cell lines coupled with prior microarray analysis identified TP53 missense mutations in 3 cell lines (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Among the gene changes they confirmed using RT-qPCR and IHC analysis, we also saw elevated expression of MMP3, SLC2A1, DKK3, POSTN, and ASPN in OSA tumors compared to normal bone samples. A recent article reported loss of PTEN expression in canine OSA cell lines (POS/HMPOS) but continued expression of RB1 in all four tested cell lines 30 . WES analysis of 8 canine OSA cell lines coupled with prior microarray analysis identified TP53 missense mutations in 3 cell lines (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Canine OSA remains challenging to treat and carries a poor prognosis due to the very aggressive and metastatic nature of the tumors. Given how common OSA is in dogs and likely genetic contribution to OSA in large breeds, we (16) and others (25,(41)(42)(43) have sought to extend understanding of the molecular determinants of OSA in dogs and to compare these results to those obtain from OSA from people.…”
Section: Discussionmentioning
confidence: 99%
“…22 In previous research, a comprehensive single-nucleotide polymorphism array and analysis of intratumoral heterogeneity was conducted using whole genome-amplified DNA retrieved from culture cells or frozen tissues isolated by laser capture microdissection (LCM) or cell sorting. [23][24][25][26] The application of WGA to cytological specimens was first reported by Beltinger et al in 1997. 27 Subsequently, Murphy et al reported genome structural variant analysis and single nucleotide variant (SNV) analysis using a large number of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The MDA method amplifies genomic DNA with a lower error rate than other methods 21 ; therefore, it is applied in the detection of somatic variants 22 . In previous research, a comprehensive single‐nucleotide polymorphism array and analysis of intratumoral heterogeneity was conducted using whole genome‐amplified DNA retrieved from culture cells or frozen tissues isolated by laser capture microdissection (LCM) or cell sorting 23–26 …”
Section: Introductionmentioning
confidence: 99%